Pengaruh Brand Image, Promosi dan Online Customer Review Terhadap Minat Beli di E-commerce Shopee - Agustina, Mila; Purba, Tiur Niari (SJEE (Scientific Journals of Economic Education), 2025)
The rapid development of technology in Indonesia has driven a shift in consumer behavior from conventional shopping to digital shopping through e-commerce platforms. E-commerce makes it easier for consumers to shop anytime and anywhere. Shopee, as one of the largest e-commerce platforms in Indonesia, has successfully attracted consumer attention through various strategies such as promotions, visual representation, and customer reviews. This study aims to analyze the factors influencing consumer purchase intention on the Shopee platform, particularly related to brand image, promotions, and online customer reviews. The research findings show that Shopee's strong brand image significantly contributes to consumer trust and purchase intention. Promotions such as flash sales, shopping vouchers, and free shipping are the main attractions that encourage consumers to make immediate transactions. Additionally, customer reviews play an important role in shaping consumer perceptions of product and service quality. Positive reviews can increase purchase intention, while negative reviews can reduce consumer trust, even though Shopee has a good reputation as a platform. User experience is also a determining factor in purchase intention, especially if the Shopee application does not function optimally or if there are issues with the delivery process. With the increasingly competitive e-commerce landscape, Shopee must continue to adapt to market trends, balance promotional activities with brand image reinforcement, and improve service quality based on customer feedback. This study is expected to provide insights for e-commerce companies in designing effective marketing strategies to enhance consumer purchase intention